Analisis Pengaruh Standar Pelayanan Minimal (SPM) Terhadap Pertumbuhan Ekonomi Melalui Kesejahtraan Masyrakat Di Kalimantan Tengah - Rahman Rahman; Alexandra Hukom (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The aim of this research is to find out whether there is an influence of Minimum Service Standards (in the fields of Education, Health and Infrastructure) on community welfare and economic growth in Central Kalimantan Province and whether welfare influences Community Economic Growth in Central Kalimantan? The data used is data originating from the relevant agencies, namely the Central Kalimantan Central Statistics Agency (BPS), and the SPM Minimum Service Standards Reporting of the Directorate General of Domestic Development. The analysis method used is path analysis. The research results prove that minimum service standards in the fields of education, health and infrastructure do not have a significant effect on increasing the welfare of the HDI community, and have no effect on increasing economic growth in Central Kalimantan.